2014
DOI: 10.1016/j.agee.2014.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen in soil and vine roots in harrowed and grass-covered vineyards

Abstract: a b s t r a c tTo examine the effects of vineyard soil management on soil C and N content and quality, we studied harrowed and grass-covered vineyards on a soil developed on plio-pleistocene, marine sediments. A soil naturally covered by grasses adjacent to the vineyards served as control. To reach this goal, we assessed (1) the distribution of C and N and their 13 C and 15 N signatures in different soil organic matter pools, (2) the amount of C and N as live and dead vine fine roots and their 13 C, 15 N and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 70 publications
2
47
1
Order By: Relevance
“…Consistent with our results, a significant positive effect of vines on total organic C and N content was reported in a vineyard ecosystem [19]. Several reasons may explain this phenomenon.…”
Section: Effects Of Liana On Soc and Tnsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with our results, a significant positive effect of vines on total organic C and N content was reported in a vineyard ecosystem [19]. Several reasons may explain this phenomenon.…”
Section: Effects Of Liana On Soc and Tnsupporting
confidence: 81%
“…Well-developed root systems of lianas [16] could impact soil physicochemical property, such as soil texture and C substrate availability during root growth and turnover [17,18]. For example, it has been found that soil organic C (SOC) and total nitrogen (TN) content were increased because of root turnover and rhizodeposition in an agricultural vineyard [19]. Additionally, lianas contribute more than 30% of total annual leaf litterfall in the tropical forest [16], thus can regulate soil C availability through changing litter quality and quantity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides favouring soil erosion, traditional tillage has been reported to be unsustainable in 40 terms of SOM and nutrient depletion (Ruiz-Colmenero et al 2013). Conversely, the combination of 41 no-tillage and permanent grass cover in the inter-row may represent an optimal solution for 42 improving aggregation and SOM protection, that is also feasible as the competition between the 43 herbaceous cover and grapevines often does not reduce yields even in rain-fed Mediterranean 44 environments (Marques et al 2010;Agnelli et al 2014;Mercenaro et al 2014). Grasses contribute 45 to organic matter input while no-tillage reduces soil macroaggregate turnover, which is crucial for C 46 sequestration in stable microaggregates.…”
Section: Introductionmentioning
confidence: 99%
“…As recently described by Ruiz-Colmenero et al (2013) and Agnelli et al (2014), a greater organic-matter accumulation is fostered by the presence of the grass cover and the absence of tillage. In the Vosne-Romanée area in Burgundy, Landry et al (2005) showed that glyphosate and its metabolite (AMPA) leached in greater amounts through a chemically treated bare Calcosol than through a vegetated Calcosol.…”
Section: Outlook: Terroir Sustainability Assessment and The Design Ofmentioning
confidence: 64%